2009
DOI: 10.1055/s-0029-1214237
|View full text |Cite
|
Sign up to set email alerts
|

Severe Intraventricular Hemorrhage in Preterm Infants: Comparison of Risk Factors and Short-Term Neonatal Morbidities between Grade 3 and Grade 4 Intraventricular Hemorrhage

Abstract: Grade 3 intraventricular hemorrhage (IVH) (without parenchymal involvement) and grade 4 IVH (with parenchymal involvement) are often combined into description of a single entity, usually "severe" IVH, despite different long-term neurodevelopmental outcome. Although risk factors for severe IVH have already been well described, it is not known if these risk factors and associated short-term neonatal morbidities are different for grade 3 and grade 4 IVH, and indeed, this clustering of grade 3 and grade 4 IVH into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
42
2
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(58 citation statements)
references
References 18 publications
9
42
2
3
Order By: Relevance
“…12 In another study done by Linder N et al it was seen that use of inotropes was associated with increased risk of IVH (p value 0.06). 13 Hypotension was also found to be significantly associated with IVH in a study done by Sarkar S et al 14 Sepsis (both culture positive and negative) was seen in 32 babies out of 104. Of them 16(50%) babies developed IVH (OR 23.0; CI:5.97-88.52; p value <0.001).…”
Section: Outcomementioning
confidence: 90%
See 1 more Smart Citation
“…12 In another study done by Linder N et al it was seen that use of inotropes was associated with increased risk of IVH (p value 0.06). 13 Hypotension was also found to be significantly associated with IVH in a study done by Sarkar S et al 14 Sepsis (both culture positive and negative) was seen in 32 babies out of 104. Of them 16(50%) babies developed IVH (OR 23.0; CI:5.97-88.52; p value <0.001).…”
Section: Outcomementioning
confidence: 90%
“…13 Sarkar S et al and Lee J Y et al also showed in their studies that neonatal sepsis is a major risk factor for IVH. 14,15 It was also shown by Adegoke SA et al that neonatal sepsis brings an increased risk for IVH in VLBW babies. 16 Hence neonatal sepsis and hypotension in these preterm babies pose the infant at great risk of intraventricular haemorrhage which increases the morbidity and mortality in this population significantly.…”
Section: Outcomementioning
confidence: 90%
“…Several variables that are risk factors for IVH 14,15,18 are increasing in incidence over time in Nova Scotia, which may help explain the increasing IVH incidence. These include infant CPR and inotrope use.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] All of these variables are considered fundamental aspects of neonatal intensive care management. However, the optimization and standardization of care to promote improved neurodevelopmental outcomes is hindered by an inability to demonstrate clear linearity between a specific care strategy and neurodevelopmental outcome.…”
Section: Introductionmentioning
confidence: 99%